THE STRUGGLE AGAINST RACISM REFLECTED IN LANGSTON HUGHES’S SELECTED POEMS - Mutia Irhamni (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2022)
The objective of this study is to find out the sense of struggling and the forms of racism toward  Black Americans in Langston Hughes selected poems titled  Advertisement For The Waldorf – Astoria, As I Grew Older, Children’s Rhyme, I, Too,  Theme for English B, Negro Mother, Demand  Democracy  Continue to Dream  The Negro Speaks to the River. In order to  get the objective of the study the researcher uses the theory of racism with a descriptive qualitative method by Miles and Huberman. Forms of racism are explained in the utterances includes personally –mediated, Internalized, and institutional racism. The meaning of struggling is to encourage the awareness of racial pride and to persuade  that black people may also get the same equality and rights in all aspects of their lives. In analyzing the object of the study, there are four techniques that are cooperated in finding and collecting data. They are data collection data condensation, data display, and conclusion. The  Result of this research is to conclude about Black Americans' identity.